2016
DOI: 10.17795/jjnpp-25352
|View full text |Cite
|
Sign up to set email alerts
|

Efflux MexAB-Mediated Resistance in Multidrug and Pan-Drug Resistant Strains of Pseudomonas aeruginosa Isolated From Patients With Burn and Wound Infections

Abstract: Background: The emergence of highly drug resistant Pseudomonas aeruginosa in burn wounds is becoming a challenging problem for infection control programs. Today, it has been shown that antibiotic resistance in P. aeruginosa is the result of synergism between membrane permeability and multidrug resistance (MDR) efflux pumps. Objectives: The aim of this study was to investigate MDR and pan-drug resistance (PDR) in P. aeruginosa and detection of the presence of efflux pump MexAB genes by the polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(20 reference statements)
3
2
0
Order By: Relevance
“…Our data showed high prevalence of MDR among the isolated strains (70%), and only (5.5%) of the isolates were PDR. In concordance with our results, a study from Iran published in 2016, reported high MDR rate in P. aeruginosa isolates (66%) from burns unit and only one strain was PDR (0.66%) [30].…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed high prevalence of MDR among the isolated strains (70%), and only (5.5%) of the isolates were PDR. In concordance with our results, a study from Iran published in 2016, reported high MDR rate in P. aeruginosa isolates (66%) from burns unit and only one strain was PDR (0.66%) [30].…”
Section: Discussionsupporting
confidence: 93%
“…This result correlates with the earlier study conducted in Iran documenting 90% positivity for the gyrA mediated ciprofloxacin resistant strains of A. baumannii [13]. In addition, gyrA mediated ciprofloxacin resistance is high when compared to the efflux pump mediated resistance which is considered as a secondary mechanism in inducing ciprofloxacin resistance among A. baumannii [14]. This documents the high-level resistance against fluoroquinolones mediated by gyrA and parC which is normally associated with a double mutation rather than multiple mutations recorded in other gram negative bacilli such as E.coli [15,16].…”
Section: Resultssupporting
confidence: 90%
“…In this study, the most effective drugs against P. aeruginosa infections were colistin (100%) and polymyxin B (98%), while the least effective drugs were cefepime (20%) and ceftazidime (16%). Our results are near to results of Khoravi & Mohammadian 21 , who reported that the most effective antibiotic against P. aeruginosa was polymyxin B (96%), and the least effective one was cefepime (20%). Also, a study in Egypt 22 reported that the most effective antibiotic against P. aeruginosa was colistin (84%), whereas the least effective ones belonged to 3 rd generation cephalosporins.…”
Section: Discussionsupporting
confidence: 78%